A Supramolecular Catalyst Self-Assembled From Polyoxometalates and Cationic Pillar[5]arenes for the Room Temperature Oxidation of Aldehydes - Zeng, Mengyan; Chen, Kun; Tan, Junyan; Zhang, Jie; Wei, Yongge (Frontiers in Chemistry, 2018)
Oxidizing aldehydes to generate carboxylic acids is a crucial reaction in nature and in chemical industry. The aldehyde oxidation, an easily achieved process in liver cells, is inert towards autoxidation in industrial production and difficultly achieved under enzymatic condition (in water, at pH 7, at room temperature). Herein, we prepared a supramolecular catalyst which are nanospheres assembled in aqueous media by chromium centered Anderson polyoxometalates Na3[CrMo6O18(OH)3] (namely, CrMo6) and cationic pillar[5]arenes (namely, P5A) with ten positive charges which can be used as the phase transfer catalysts (PTCs). This supramolecular catalyst was exploited on aldehydes oxidation under enzymatic condition with relatively good conversion. Through DLS monitoring, the diameters of nanospheres were variable while changing the charge ratios of the ionic complexes (P5A-CrMo6), and it is probably because of the closer charge ratios causing the more compact assemblies. Also, the nano-morphologies were monitored by TEM and SEM, and the nanostructures were characterized by zeta potential, the X-ray energy-dispersive spectroscopy (EDS), elemental analysis.